Co kryje się za słowem "quincunx"? Rzecz o konferencji pt. "Stanisław Orzechowski - pisarz polityczny. W pięćsetlecie urodzin" - Magryś, Roman (Wydawnictwo Uniwersytetu Rzeszowskiego, 2014)
The article presents a report on the scholarly meeting organized in Przemyśl, in October 2013 by Rzeszow University, Jagiellonian University and the Society of Science Lovers in Przemyśl, which was devoted to an eminent Polish Renaissance humanist Stanisław Orzechowski. It contains a brief review of all the papers delivered during the conference as well as a succinct sketch of Orzechowski’s biography, including his most significant literary accomplishments.
What is behind the Word ”quincunx”? A Word on the Conference: "Stanisław Orzechowski a Political Writer. On the Five Hundredth Anniversary of His Birth"
Keywords: celibat; filozofia; heretyk; katolicyzm; kultura; małżeństwo; moralność; osobowość; papież; polityka; prawo; prawosławie; protestantyzm; reformacja; religia; renesans; Stanisław Orzechowski; społeczeństwo; szlachta; teokracja; celibacy; philosophy; heretic; Catholicism; culture; marriage; morality; personality; pope; politics; law; the Orthodox Church; Protestantism; Reformation; religion; the Renaissance; society; nobility; theocracy